2012
DOI: 10.1063/1.3691945
|View full text |Cite
|
Sign up to set email alerts
|

Lone conduction band in Cu2ZnSnSe4

Abstract: Band gap control via tuning of inversion degree in CdIn2S4 spinel Appl. Phys. Lett. 100, 102112 (2012) Direct imaging and optical activities of stacking faults in 4H-SiC homoepitaxial films J. Appl. Phys. 111, 053513 (2012) Steady state and transient electron transport properties of bulk dilute GaNxAs1−x J. Appl. Phys. 111, 053703 (2012) Efficient algorithm of the transcorrelated method for periodic systems J. Chem. Phys. 136, 094108 (2012) Valence band structure in boron-zinc oxide films characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…The Zn-Sn layer ordering makes a relatively smaller effect because it influences only the ordering with ST and PMCA as the two end point constituents, and they are both derived from the CuAu (CA) structure of the ternary compounds. 10 The effect of Cu-Zn ordering is the smallest, consistent with the fact that Cu and Zn are same row neighbors in the Periodic Experiment studies show that the band gap of CZTSe is around 1 eV, 4,18 however, it generally decreases with increasing of the annealing temperature, and the deviation of the band gap is as large as 0.12 eV. 18 Our calculation shows that lower band gap polytypes have higher formation energy, which are more likely to form as temperature increases, resulting in the reduced band gap.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The Zn-Sn layer ordering makes a relatively smaller effect because it influences only the ordering with ST and PMCA as the two end point constituents, and they are both derived from the CuAu (CA) structure of the ternary compounds. 10 The effect of Cu-Zn ordering is the smallest, consistent with the fact that Cu and Zn are same row neighbors in the Periodic Experiment studies show that the band gap of CZTSe is around 1 eV, 4,18 however, it generally decreases with increasing of the annealing temperature, and the deviation of the band gap is as large as 0.12 eV. 18 Our calculation shows that lower band gap polytypes have higher formation energy, which are more likely to form as temperature increases, resulting in the reduced band gap.…”
Section: Resultssupporting
confidence: 58%
“…This is because they contain relatively earth abundant elements, are easy to grow, and have suitable direct band gap energies in the range of 1 to 1.5 eV at their ground state, [1][2][3][4][5] which are optimal for single junction solar cell applications. 3,6 However, despite the recent extensive study and rapid progress in development of this new solar cell technology, its power conversion efficiency is still lower than the more mature technologies, such as binary CdTe or ternary Cu(In 1-x Ga x )Se 2 (CIGSe) based solar cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation of the kesterites optical properties and, in particular, their optical constants, is of great interest for both fundamental and application reasons. Some optical constants data from theoretical ab-initio calculations [7][8][9][10] and from a few experimental reports on CZTSe polycrystalline thin films 8,9,11 and bulk crystals 12 have already been reported. With the aim of get a better understanding of the optical constants, we have studied the room temperature spectroscopic ellipsometry (SE) of CZTSe bulk crystals, grown by the Bridgman method.…”
mentioning
confidence: 99%
“…The fundamental absorption edge E 0 ¼ E g is observed near 1 eV in agreement with Chen et al 10 calculations, and high energy features E 1A (E 1B ) are found at about 2.3 (4.0) eV, respectively, in agreement with the previous reports. 8,11,12 According to the Adachi's model for the dielectric function (MDF), the electronic transitions in the neighborhood of CP contribute to the features of the complex dielectric function e(E). 17 We employed this approach and modelled the pseudo-dielectric function of the CZTSe crystals.…”
mentioning
confidence: 99%